2020
DOI: 10.1371/journal.pone.0236525
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of psychological interventions on children and young people’s mental health: A systematic review and meta-analysis

Abstract: Background Over 600 RCTs have demonstrated the effectiveness of psychosocial interventions for children and young people’s mental health, but little is known about the long-term outcomes. This systematic review sought to establish whether the effects of selective and indicated interventions were sustained at 12 months. Method We conducted a systematic review and meta-analysis focusing on studies reporting medium term outcomes (12 months after end of intervention). Findings We identified 138 trials with 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Most of the existing evidence for the longer-term effectiveness of youth mental health interventions is based on relatively lengthy (16.5 sessions on average), disorder-specific treatment protocols [ 3 ]. It is noteworthy that the longer-term effect of this brief, transdiagnostic, problem-solving intervention on mental health symptoms, although small, is comparable to the long-term outcomes achieved by more intensive interventions, mostly delivered by specialists [ 3 , 20 ]. Further, the effect on mental health symptoms was accompanied by a comparable effect on the YTP (an idiographic measure of problems’ meaningful to a young person), as well as significant improvements in domains of functional impairment and perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the existing evidence for the longer-term effectiveness of youth mental health interventions is based on relatively lengthy (16.5 sessions on average), disorder-specific treatment protocols [ 3 ]. It is noteworthy that the longer-term effect of this brief, transdiagnostic, problem-solving intervention on mental health symptoms, although small, is comparable to the long-term outcomes achieved by more intensive interventions, mostly delivered by specialists [ 3 , 20 ]. Further, the effect on mental health symptoms was accompanied by a comparable effect on the YTP (an idiographic measure of problems’ meaningful to a young person), as well as significant improvements in domains of functional impairment and perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…This review focuses on psychological intervention because of the rarity of primary research trials of pharmacological interventions with young people, 37 and reported longer-term benefits of psychological interventions, including reducing the burden of ongoing mental health disorders into adulthood and improved quality of life, as highlighted in recent evidence. 38,39 In addition, in light of the COVID-19 pandemic, mental health presentations to the PED are expected to continue exponentially, therefore a new review must be conducted to guide future suicide prevention. 6 This review restricted focus to randomised controlled trials (RCTs) only, as they are considered to provide the strongest test of whether an intervention has an effect.…”
Section: The Current Reviewmentioning
confidence: 99%
“…In response to the growing demand for MH care among CYP, various preventive interventions, including school-based programs, have been implemented across different settings, yielding positive impacts on the wellbeing of CYP by reducing depression and anxiety through the provision of coping strategies and interventions ( 27 ). Moreover, a broad range of intervention approaches, including psychosocial interventions, have been successfully implemented in a variety of health and community settings ( 22 , 28 32 ). Additionally, parent and family-focused interventions (including psychoeducation, parent and family-skills training, behavioral, psychosocial, and cognitive behavioral therapy [CBT]) are known to be efficacious in improving CYP’s MH outcomes as well as parenting behaviors and family functioning ( 30 , 33 ).…”
Section: Introductionmentioning
confidence: 99%